Applying service performance guarantees to reduce risk perception in the purchase and consumption of higher education / Nooraini Mohamad Sheriff and Faridah Hassan - Mohamad Sheriff, Nooraini; Hassan, Faridah (ACRULeT, Faculty of Education & UiTM Press, 2006)
The intangible nature of education is one contributor to consumers’ perception of risk prior to their purchase and consumption. This risk includes: functional risk, financial risk, temporal risk, physical risk, psychological risk and social risk. The presence of these risks often makes consumer evaluation prior to purchase and consumption difficult. Invoking a service guarantee is a platform available to enable higher educational institutions to minimize such risk perception so as to induce purchase. Specifically, service guarantee for higher education entails the application of teaching performance guarantee. This form of guarantee focuses on two important customer groups of higher educational institutions namely, students and faculty members, and focuses only on a specific performance aspect such as instructor’s performance. Thus, if students are dissatisfied with an instructor’s performance they are entitled to receive their money back. The imposition of such a teaching performance guarantee would implicate instructor’s accountability for certain aspects of their performance. It also establishes a mechanism to solicit feedback to better understand why and how instructors fail. Consequently, service performance guarantee creates a high level of customer focus and signals instructors’ care towards students.